Introduction - Wodecka-Hyjek, Angelika; Chlipała, Paweł (Journal of Public Governance, 2025)
Urban management encompasses many problem areas that shape residents’ quality of life.  A focus on the quality of life is gaining importance alongside the growing awareness of public administration employees, managers, as well as residents of urban agglomerations in the field of sustainable development and social responsibility. Government institutions, local authorities, and enterprises increasingly recognise the benefits associated with societal well-being. A well-managed city provides its residents with opportunities for comfortable living, rest, and personal development, while these factors enhance employee productivity and attract investors and tourists, too. At the same time, residents’ expectations are rising with regard to access to housing, adequate transport infrastructure, educational opportunities, cultural offerings, leisure and recreational services, and many other aspects. The voices of residents, voters, and stakeholders – all of whom may shape the tone of the debate on urban management strategies – are becoming increasingly significant.This issue of the Journal of Public Governance addresses three areas of urban management, covering topics related to social services in the field of child welfare, the perception of key socioeconomic challenges by the political authorities of district towns in the Silesian Province, and the determinants of regional economic growth in Poland, with particular emphasis on the role of residential property prices.